2017
DOI: 10.5694/mja17.00686
|View full text |Cite
|
Sign up to set email alerts
|

COPD‐X Australian and New Zealand guidelines for the diagnosis and management of chronic obstructive pulmonary disease: 2017 update

Abstract: Chronic obstructive pulmonary disease (COPD) is characterised by persistent respiratory symptoms and chronic airflow limitation, and is associated with exacerbations and comorbidities. Advances in the management of COPD are updated quarterly in the national COPD guidelines, the COPD-X plan, published by Lung Foundation Australia in conjunction with the Thoracic Society of Australia and New Zealand and available at http://copdx.org.au. Main recommendations: Spirometry detects persistent airflow limitation (post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
364
1
23

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(390 citation statements)
references
References 61 publications
2
364
1
23
Order By: Relevance
“…Patients with chronic respiratory diseases, such as COPD or pulmonary fibrosis, experience a complex and often unpredictable disease course,4 which is characterised by a gradual decline, interrupted by sudden and life-threatening exacerbations 5 6. As the disease progresses, complications may become more frequent and complex 7. Disease progression may also lead to a variety of symptoms, such as dyspnoea, and comorbidities, which can reduce the quality of life of patients substantially 7…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with chronic respiratory diseases, such as COPD or pulmonary fibrosis, experience a complex and often unpredictable disease course,4 which is characterised by a gradual decline, interrupted by sudden and life-threatening exacerbations 5 6. As the disease progresses, complications may become more frequent and complex 7. Disease progression may also lead to a variety of symptoms, such as dyspnoea, and comorbidities, which can reduce the quality of life of patients substantially 7…”
Section: Introductionmentioning
confidence: 99%
“…Patients, their relatives and healthcare professionals (HCPs) are faced with treatment decisions throughout the disease course. Acute deterioration of health can,7 for instance, result in respiratory failure requiring mechanical ventilation and the necessity of having to make ad hoc decisions on how to proceed 8…”
Section: Introductionmentioning
confidence: 99%
“…The authors included studies that reported on interventions specifically targeting people with COPD living in rural or remote locations in Australia or New Zealand. These countries share a common guideline for the management of COPD, specified by the Thoracic Society of Australia and New Zealand 15 , which means interventions in the review were more likely to fall within the COPDX guidelines and be relevant to the investigators' practice. While reviewing only literature based in rural or remote areas substantially limited the scope of the review, it was recognised that the context of rural health is geographically, sociologically and demographically different to metropolitan settings 18 .…”
Section: Discussionmentioning
confidence: 99%
“…It has highlighted a need to review the key success factors for COPD management interventions internationally and in urban Australia and New Zealand and determine the transferability of intervention design to rural areas. 15 showing the process of study selection in a systematic review of the availability and cost effectiveness of chronic obstructive pulmonary disease management interventions in rural Australia and New Zealand. The authors included studies that reported on interventions specifically targeting people with COPD living in rural or remote locations in Australia or New Zealand.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 We assumed that patients attending an ED for care had at least a moderate exacerbation of COPD. Published COPD guidelines were used as the reference standard for treatment.…”
Section: Copd In Edmentioning
confidence: 99%